How ligands modulate the gastric H,K-ATPase activity and its inhibition by tegoprazan - Cerf, Nicole Talia (2024)
The introduction of potassium-competitive acid blockers (P-CABs) has been a major innovation in gastric H,K-ATPase inhibition and many laboratories are actively engaged in the development of novel molecules within this class. This work investigates the interaction between H,K-ATPase and tegoprazan, a representative of the P-CABs group, in terms of K+ and H+ binding, through functional and structural analyses. First, by studying the H,K-ATPase activity we found a model to describe the non-Michaelis Menten kinetics through a "ping-pong" mechanism that explains a stoichiometry of 1 H+, 1 K+, and 1 ATP molecule, but also considering the influence of H+ on the ionization states of the protein. A kinetic evaluation of the inhibition of tegoprazan denotes the binding to two different intermediates states with apparent Kd (μM) 0.56 ± 0.04 and 2.70 ± 0.24 at pH 7.2. Molecular dynamics simulations revealed important changes in the interactions of tegoprazan with the transmembrane residues depending on whether the site contains K+ or not. This explains the decrease in affinity as a function of K+ concentration observed in the kinetic experiments. On the other hand, the structures predict that the protonation of tegoprazan is responsible for the change in its dihedral angle. The rotation of the benzimidazole ring allows the inhibitor to be positioned further into the luminal cavity, a situation compatible with the higher inhibition affinity of H,K-ATPase measured at low pH. Results presented herein will provide a basis for the rational design of novel P-CABs ligands.